2019
DOI: 10.31351/vol28iss2pp37-45
|View full text |Cite
|
Sign up to set email alerts
|

Ex-Vivo Absorption Study of a Novel Dabigatran Etexilate Loaded Nanostructured Lipid Carrier Using Non-Everted Intestinal Sac Model

Abstract: Abstract The purpose of our study was to develop Dabigatran Etexilate loaded nanostructured lipid carriers (DE-NLCs) using Glyceryl monostearate and Oleic acid as lipid matrix, and to estimate the potential of the developed delivery system to improve oral absorption of low bioavailability drug, different Oleic acid ratios effect on particle size, zeta potential, entrapment efficiency and loading capacity were studied, the optimized DE-NLCs shows a particle size within the nanorange, the zeta potential (Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Formula 1: Cold homogenization was used to create GCV-NLCs, and the following technique was used with slight changes. 6 The solid lipid PA and OA as a liquid lipid were melted, then 1% transcutol was added as a solubilizer and mixed into the melted lipid. Finally, 75 mg of GCV was added, and the mixture was magnetically stirred for two minutes.…”
Section: Preparation Of Drug-loaded Nlcmentioning
confidence: 99%
See 1 more Smart Citation
“…Formula 1: Cold homogenization was used to create GCV-NLCs, and the following technique was used with slight changes. 6 The solid lipid PA and OA as a liquid lipid were melted, then 1% transcutol was added as a solubilizer and mixed into the melted lipid. Finally, 75 mg of GCV was added, and the mixture was magnetically stirred for two minutes.…”
Section: Preparation Of Drug-loaded Nlcmentioning
confidence: 99%
“…After the materials were diluted with double-distilled water, the particle means diameter and PDI measurements were made. 6…”
Section: Particle Size (Ps) and Poly Dispersity Index (Pdi) Determina...mentioning
confidence: 99%
“…The hydrodynamic diameters and size distribution (polydispersity index) of sHDL were determined by dynamic light scattering system (DLS) using a 90Plus Particle Size Analyzer (Brookhaven Instruments Corporation, USA). Each sample was diluted with equal volume of distilled water (DW), and analyzed at temperature of 25⁰C (18) .…”
Section: Characterization Of Shdl Nanoparticles Determination Of Part...mentioning
confidence: 99%
“…Ex vivo study was achieved on fasted male sheep weighing about 16 kg using the non-everted sac method. [32][33][34] The animal slay and anatomize according to the legal method achieved in the university of Baghdad/ college of pharmacy. The small intestine was isolated and carefully removed mesentery matter and washed the small intestine by cold normal saline solution.…”
Section: Ex-vivo Intestinal Permeation Studymentioning
confidence: 99%
“…It was observed that the pure drug suspension gives a lower permeation coefficient in comparison to all optimized felodipine LPHNs formulations(F1-F9) because that felodipine LPHNs formulations belong to lipid base nanosystem that increases solubility and intestinal permeation also, nanoscale of these hybrid carriers provide large surface area for molecular felodipine libration and rapid absorption to the systemic circulation. [32][33][34] The analysis of variance indicates a significant(p-value <0.05) correlation between the blend of PEG laurate: polysorbate 80: propylene glycol contents, lipid content, and chitosan polymer and ex vivo intestinal permeation parameter.…”
Section: Ex-vivo Intestinal Permeation Studymentioning
confidence: 99%